2020
DOI: 10.1177/2045894020908782
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of lung cell populations in idiopathic pulmonary arterial hypertension

Abstract: Despite recent improvements in management of idiopathic pulmonary arterial hypertension, mortality remains high. Understanding the alterations in the transcriptome–phenotype of the key lung cells involved could provide insight into the drivers of pathogenesis. In this study, we examined differential gene expression of cell types implicated in idiopathic pulmonary arterial hypertension from lung explants of patients with idiopathic pulmonary arterial hypertension compared to control lungs. After tissue digestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 91 publications
(110 reference statements)
4
78
0
Order By: Relevance
“…ScRNA-Seq analyses in human PAH patients have uncovered the upregulation of angiogenesis-associated genes in ECs such as endoglin (ENG), NOTCH1 and KDR, together with genes involved in SMC migration and proliferation such as PDGFB and FGFR1, as well as vasoconstrictor endothelin 1 (EDN1) [74]. Interestingly, apelin (APLN) and apelin cleaving enzyme lysosomal pro-X carboxypeptidase (PRCP) were elevated in PAH samples [74], contradicting the previously reported reduction in APLN and PRCP expression in pulmonary artery ECs isolated from PAH patients in vitro and the regression of PAH in mice after APLN administration [75,76]. Genes upregulated in SMCs and pericytes were related to ECM components that support vessel wall remodeling and increased ECM stiffness [74].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…ScRNA-Seq analyses in human PAH patients have uncovered the upregulation of angiogenesis-associated genes in ECs such as endoglin (ENG), NOTCH1 and KDR, together with genes involved in SMC migration and proliferation such as PDGFB and FGFR1, as well as vasoconstrictor endothelin 1 (EDN1) [74]. Interestingly, apelin (APLN) and apelin cleaving enzyme lysosomal pro-X carboxypeptidase (PRCP) were elevated in PAH samples [74], contradicting the previously reported reduction in APLN and PRCP expression in pulmonary artery ECs isolated from PAH patients in vitro and the regression of PAH in mice after APLN administration [75,76]. Genes upregulated in SMCs and pericytes were related to ECM components that support vessel wall remodeling and increased ECM stiffness [74].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Interestingly, apelin (APLN) and apelin cleaving enzyme lysosomal pro-X carboxypeptidase (PRCP) were elevated in PAH samples [74], contradicting the previously reported reduction in APLN and PRCP expression in pulmonary artery ECs isolated from PAH patients in vitro and the regression of PAH in mice after APLN administration [75,76]. Genes upregulated in SMCs and pericytes were related to ECM components that support vessel wall remodeling and increased ECM stiffness [74]. Furthermore, bioinformatic analyses of regulatory networks derived a number of transcription factors such as SOX18, STRA13, LYL1 and TFDP1 [74], which are likely to play an important role in ECs in PAH.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular composition of the lung is 40-50% endothelial cells, which differentiate in parallel with epithelial cells to form gas exchange units which are in contact with the external environment and thus need to ensure a rapid immune response (30). In lung diseases, including infections, the transcriptomes of endothelial cells, pericyte/smooth muscle cells, fibroblasts, and macrophage clusters showed that endothelial cells had the most differentially expressed gene profile compared to other cell types (31). We speculated that if we found common differentially expressed genes shared between the two cell types and which could be affected by SARS-CoV-2 infection, then we may be able further to understand the link between COVID-19 and associated endothelium injuries.…”
Section: Lung Single-cell Expression Of Degsmentioning
confidence: 99%
“…In the past few decades, microarray analysis has been used for gene-wide expression pro ling in lung tissues or peripheral blood from PAH patients or experimental animals to de ne PAH's pathobiology [6][7][8][9][10]. However, the ndings are inconsistent between different researches, which may be caused by various analysis platforms, limited sample sizes, different methods, no classi cation of PAH, and not for IPAH.…”
Section: Introductionmentioning
confidence: 99%